Local Average Signal Strength Estimation for Indoor Multipath Propagation - Obeidat, Huthaifa; Alabdullah, Ali A. S.; Ali, Nazar T.; Asif, Rameez; Obeidat, Omar; Bin-Melha, Mohammed S. A.; Shuaieb, Wafa; Abd-Alhameed, Raed A.; Excell, Peter (IEEE access, 2019)
A comprehensive study of approaches for the estimation of the local average of the received signal strength (RSS) for indoor multipath propagation is presented. The effects of the required number of the RSS data samples and the Euclidean distances between the neighboring samples are investigated over 1D, 2D, and 3D configurations. It was found that the effect of fast fading was reduced to an acceptable level using a 2D horizontal arrangement with a relatively large spacing configuration. Furthermore, averaging was enhanced with a larger spacing compared to smaller spacing when considering the same number of samples.